Preparation and Characterization of Platinum and Rhodium Nanoparticles Stabilized by Functional Polymer Microspheres - Liu, Wei; Wang, Jing; Chen, Xuehua; Wei, Junfu; Yang, Xinlin (Asian Journal of Chemistry, 2015)
The platinum and rhodium nanoparticles with different sizes were synthesized by in situ reduction of the metallic precursor, supported on the highly crosslinked monodisperse poly(DVB-co-AA), poly(EGDMA-co-VPy) and poly(EGDMA-co-HEMA)-SH microspheres with different functional groups on the surface, which were prepared by distillation-precipitation polymerization. The Pt and Rh nanoparticles were characterized by TEM, which show high distribution on the polymer supporters and narrow-dispersed diameters. The interaction between Pt and Rh nanoparticles and the functional groups of polymer supports were investigated by X-Ray photoelectron spectroscopy (XPS). It is found that the sizes of metallic particles have relationship with the interaction of metals and functional groups and electronegativity of metals: with respect to the same metal, the stronger interaction, the smaller diameter of the nanoparticle; for the same polymer supporter, the larger electronegativity of the noble metals, the bigger size of the nanoparticle.